GAMELAN LUNTHUNG KARYA WIDODO DONOSUKARTO DESA KADOKAN, KECAMATAN GROGOL, KABUPATEN SUKOHARJO - Panggiyo Panggiyo (Institut Seni Indonesia Surakarta, 2012)
According to the empirical experience, basically all metals can be used as materials for gamelan. However, the resulting master gamelan been generally designed for adults. Form and larasan (steming) gamelan often cause problems when used for the race musical elementary school children (SD). In terms of shape and size, posture mean that small children will find it difficult at times to reach Ricikan (instrument) bonang. On the side of the barrel (scales) ambitus child becomes a fairly complicated issue for children. At the till, backgrounds aged children who are close to the joyous feeling of typical children become its own problems when faced with factors belonging gending garap from parents (adults). In a situation like this came the idea to create a gamelan Suroso that can meet the needs of standard forms, tunings and feeling young. Tit for tat, Suroso ideas taken seriously by Widodo Donosukarto, a master craftsman from the village gamelan reliable Kadokan, Grogol, Sukoharjo. In 2002 Widodo Donosukarto began his experiments made gamelan largely shaped kemanak. At the beginning of the process of manufacture gamelan Widodo Donosukarto often fails. But with unyielding spirit, finally in 2005 Widodo Donosukarto succeeded in realizing the coveted gamelan. Since the technique of making the model gemelan kemanak by way lunthung (rolled), the new gamelan called Gamelan Lunthung. During the experiment (2002-2005) Widodo Donosukarto only able to make two sets of Gamelan Lunthung. Gamelan The first was in the child’s home law (the Netherlands) in Amsterdam, the orchestra both at home Widodo Donosukarto. Data obtained through the study of literature and interviews. The analysis was conducted mostly take the data obtained from interviews with sources that Widodo Donosukarto. Interviews were conducted in 2009-2011 at home Widodo Donosukarto, Kadokan Village, District Grogol, Sukoharjo. Key words : Widodo Donosukarto, Gamelan Lunthung